Bacteriological studies of bile from the gallbladder in patients with carcinoma of the gallbladder, cholelithiasis, common bile duct stones and no gallstones disease - Csendes, A; Becerra, M; Burdiles, P; Demian, I; Bancalari, K; Csendes, P (The European journal of surgery, 1994)
To compare the presence of bacteria of bile from the gallbladder in control subjects, patients with gallstones, and patients with carcinoma of the gallbladder. Prospective open study. University department of surgery. 372 patients of whom 36 had no signs of gallbladder disease; 211 underwent cholecystectomy for either symptomatic gallstone disease (n = 165) or acute cholecystitis (n = 46); 67 had common bile duct stones and 58 were operated on for carcinoma of the gallbladder. Aspiration of bile from the gallbladder. Prevalence of pathogenic bacteria in bile from the gallbladder and correlations between the presence of bacteria, the presence of cancer, and age. No pathogenic bacteria were grown from the bile of the patients who had no signs of gallstones disease. Among the 165 with symptomatic gallstone disease 52 (32%) had pathogens in their bile, and among the 46 with acute cholecystitis the corresponding figure was 19 (41%) while among patients with common bile duct stones this figure was 39 (58%). Among the 58 patients with carcinoma of the gallbladder the bile grew organism in 47 (81%). Patients over the age of 60 years tended to be more likely to have organism in their bile than patients aged 60 or less, and the difference was significant for symptomatic gallstone disease (p < 0.003). Significant differences were also found between patients with symptomatic gallstone disease and those with carcinoma of the gallbladder in both age groups (p < 0.002 in each case). Most of the organism were aerobic or anaerobic Gram negative species, irrespective of type of disease or age. Bacteria may have a role in the development of carcinoma of the gallbladder.